The Role of TQM Practice in Improving Business Performance’s Pharmaceutical Industry in Indonesia - Yuli Fitriyani; Aziz Y; Rivani R; Kaltum U; Sihotang J (Jurnal Manajemen Indonesia, 2021)
The primary purpose of this study is to investigate the role of Total Quality Management (TQM) on business performance in various dimensions. This study proposes a conceptual model that intends to study several research hypotheses. The data were obtained through an online questionnaire, sent to pharmaceutical companies manufactured generic products in Indonesia. The study was conducted based on responses received from 168 valid questionnaires, and it was used partial least squares structural equation modeling (PLS-SEM) to test the hypotheses. Furthermore, we use both of reflective and formative construct with second order/higher order construct in our model of study which is rarely found in the previous study. This research analyzed the dimensions studied in different aspects. TQM variable consists of seven practice, namely management commitment, supplier quality, employee involvement, leadership management, customer orientation, continuous improvement and quality management system, and with respect to business performance, this variable was analyzed through four different perspectives, namely, financial, customer, internal business process and learning & growth. The findings indicate that companies adopt total quality management get improvement in their business performance. Leadership management has greater effect on the successful of TQM practice compared to other TQM dimensions. This study also provides a particular contribution for the companies and expect to be used as feedback related to the execution of their TQM implementation to improve their business performance. Keywords— Balanced Scorecard; Business Performance; Pharmaceutical Industry; Total Quality Management